Effects of a Dietary Approach to Stop Hypertension (DASH) Diet Intervention on Serum Uric Acid in African Americans With Hypertension. Issue 10 (21st August 2018) - Juraschek, Stephen P.; White, Karen; Tang, Olive; Yeh, Hsin‐Chieh; Cooper, Lisa A.; Miller, Edgar R.
Abstract : Objective: To examine whether partial replacement of a diet typical of the average American diet with Dietary Approaches to Stop Hypertension (DASH)–related foods in the home environment lowers the serum uric acid (UA) level in individuals with hypertension. Methods: We conducted an ancillary study of a randomized trial of African American adults with controlled hypertension from an urban clinic. Participants were assigned to either a control group or an intervention (DASH‐Plus) group. DASH‐Plus participants received coach‐directed dietary advice, assistance with purchasing DASH‐related foods (30/week), and home delivery of food via a community supermarket. Participants in the control group received a DASH diet brochure and a debit card account (30/week) to purchase foods. Serum UA levels were measured at baseline and after 8 weeks. Results: Of the original 123 randomized participants, 117 had available serum UA measurements. Seventy percent of the participants were women, the mean ± SD age was 59 ± 9.5 years, and the mean ± SD serum UA level was 6.4 ± 1.7 mg/dl. The DASH‐Plus diet did not reduce serum UA levels compared with the control diet (difference in difference –0.01 mg/dl [95% confidence interval –0.39, 0.38]). However, there was a significant trend toward a greater reduction in the serum UA level in participants with higher baseline serum UA levels ( P for trend = 0.008). Baseline changes in the serum UA level were inversely associated with changes in systolic blood pressure ( P = 0.002), diastolic blood pressure ( P = 0.001), and urinary sodium excretion ( P = 0.05). Conclusion: Overall, in African American individuals, partial replacement of a typical diet with DASH foods did not lower serum UA levels compared with a control diet. However, there was a significant trend toward a greater reduction in serum UA levels in subjects with higher baseline serum UA levels. Furthermore, changes in serum UA levels were associated with known correlates, suggesting heterogeneity of effects in the treatment and control arms. Future pragmatic studies of consumption of the DASH diet to lower serum UA levels should optimize replacement strategies and enroll individuals with hyperuricemia or gout.